L-GSH Supplementation in Conjunction With Rifampicin Augments the Treatment Response to Mycobacterium tuberculosis in a Diabetic Mouse Model - Beever, Abrianna; Kachour, Nala; Owens, James; Sasaninia, Kayvan; Kolloli, Afsal; Kumar, Ranjeet; Ramasamy, Santhamani; Sisliyan, Christina; Khamas, Wael; Subbian, Selvakumar; Venketaraman, Vishwanath (Frontiers in Pharmacology, 2022)
Both active tuberculosis (TB) and asymptomatic latent Mycobacterium tuberculosis (M. tb) infection (LTBI) cause significant health burdens to humans worldwide. Individuals with immunocompromising health conditions, such as Type 2 Diabetes Mellitus (T2DM), have a weakened ability to control M. tb infection and are more susceptible to reactivation of LTBI to active diseases. T2DM cases are known to have glutathione (GSH) deficiency and impaired immune cell function, including the granulomatous response to M. tb infection. We have previously reported that liposomal glutathione (L-GSH) supplementation can restore the immune cell effector responses of T2DM cases. However, the effects of L-GSH supplementation on the bactericidal activities of first-line anti-TB drug rifampicin (RIF) against M. tb infection have yet to be explored. The aim of this study is to elucidate the effects of L-GSH supplementation in conjunction with RIF treatment during an active M. tb infection in a diabetic mouse model. In this study, we evaluated total and reduced levels of GSH, cytokine profiles, malondialdehyde (MDA) levels, M. tb burden, and granulomatous response in the lungs. We show that L-GSH supplementation caused a significant reduction in M. tb burden in the lungs, decreased oxidative stress, and increased the production of IFN-γ, TNF-α, IL-17, IL-10, and TGF-β1compared to the untreated mice. In addition, L-GSH supplementation in conjunction with RIF treatment achieved better control of M. tb infection in the lungs and significantly reduced the levels of oxidative stress compared to treatment with RIF alone. Moreover, L-GSH in conjunction with RIF significantly increased IL-17 and TGF-β1levels, compared to treatment with RIF alone. These findings suggest potential therapeutic benefits of L-GSH supplementation in conjunction with first-line antibiotic therapy against M. tb infection in individuals with T2DM.